Pengembangan Multimedia Interaktif Berbasis Web Untuk Meningkatkan Literasi Budaya Dan Literasi Digital Siswa Kelas V SD/MI - Dewanto Muhammad Zulqadri; Burhan Nurgiyantoro (IPTEK-KOM : Jurnal Ilmu Pengetahuan dan Teknologi Komunikasi, 2023)
This research and development aims to produce web-based interactive multimedia to enhance cultural literacy and digital literacy skills of 5th grade students in elementary schools. It describes the validation results of the web-based interactive multimedia in terms of media and content suitability by experts and teachers. Additionally, it investigates the effectiveness of the web-based interactive multimedia in improving cultural literacy and digital literacy skills of 5th grade students in elementary schools. The research and development process results in a web-based interactive multimedia product that is deemed suitable based on the validation by experts and potential users. Furthermore, the product is found to be effective in enhancing cultural literacy and digital literacy skills of students based on the effectiveness test using T-test.